2001
DOI: 10.5326/15473317-37-6-537
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of once-daily clindamycin hydrochloride in the treatment of superficial bacterial pyoderma in dogs

Abstract: Twenty-one dogs with canine superficial bacterial pyoderma were treated with clindamycin at a dosage of approximately 11 mg/kg body weight, q 24 hours, given orally for 14 to 42 days. All dogs were reexamined on days 14, 28, and, if necessary, 42 and given a clinical score of excellent (i.e., complete remission), good (i.e., primary lesions resolved but secondary lesions evident), fair (i.e., partial improvement but primary lesions still evident), or poor (i.e., no improvement or worsening of the lesions). A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Many studies from various countries (Medleau et al 1986;Noble & Kent 1992;Kruse et al 1996;Stegemann et al 1996;Pellerin et al 1998;Scott et al 1998;Bloom & Rosser 2001;Holm et al 2002;Petersen et al 2002;Ganiere et al 2005;Hauschild & W ojcik 2007;Huerta et al 2011;Saridomichelakis et al 2002) have shown that the in vitro susceptibility rates of staphylococcal isolates from cases of pyoderma range from 65 to 94% and that this agent is clinically effective in 71 to 100% of affected dogs (Harvey et al 1993;Scott et al 1998;Littlewood et al 1999;Bloom & Rosser 2001). We have previously shown that, in healthy dogs, the oral dosage regimen of 11 mg/kg BW once daily has a better pharmacokinetical/ pharmacodynamical profile compared to 5.5 mg/kg BW orally twice daily (Saridomichelakis et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies from various countries (Medleau et al 1986;Noble & Kent 1992;Kruse et al 1996;Stegemann et al 1996;Pellerin et al 1998;Scott et al 1998;Bloom & Rosser 2001;Holm et al 2002;Petersen et al 2002;Ganiere et al 2005;Hauschild & W ojcik 2007;Huerta et al 2011;Saridomichelakis et al 2002) have shown that the in vitro susceptibility rates of staphylococcal isolates from cases of pyoderma range from 65 to 94% and that this agent is clinically effective in 71 to 100% of affected dogs (Harvey et al 1993;Scott et al 1998;Littlewood et al 1999;Bloom & Rosser 2001). We have previously shown that, in healthy dogs, the oral dosage regimen of 11 mg/kg BW once daily has a better pharmacokinetical/ pharmacodynamical profile compared to 5.5 mg/kg BW orally twice daily (Saridomichelakis et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The recommended dosage regimen of oral clindamycin in the dog ranges from 5.5 to 11 mg/kg body weight, given once or twice daily 11,12 . Although once‐daily administration is more convenient 1,2 and seems to be effective for the treatment of both superficial 2,13 and deep bacterial pyoderma, 14 it is unknown whether the pharmacokinetics of once‐daily dosing are comparable to twice‐daily administration.…”
Section: Introductionmentioning
confidence: 99%
“…5,11,12 In most studies, the in vitro susceptibility of staphylococcal isolates from infected canine skin to this antimicrobial agent ranges from 65 to 94%, 1,3,6,11,[13][14][15][16][17][18][19][20] and the relevant figure in Greece is 80.1%. 21 Furthermore, based on four different clinical trials, 71.4-100% of dogs with superficial or deep bacterial pyoderma were cured after clindamycin administration, 2,13,14,22 and some dogs with staphylococcal isolates showing in vitro resistance to clindamycin showed a prompt response to the treatment. 13,14 The recommended dosage regimen of oral clindamycin in the dog ranges from 5.5 to 11 mg/kg body weight, given once or twice daily.…”
Section: Introductionmentioning
confidence: 99%
“…However, no associated conditions could be noticed in the remaining 2 dogs. Simultaneously, Bloom and Rosser [8] failed to identify the underlying cause associated with pyoderma in 2 dogs out of 21 dogs. Bensignor and Germain [4] also could not identify the associated conditions in two out of 30 dogs of their study on canine recurrent pyoderma.…”
Section: Resultsmentioning
confidence: 99%
“…Efficacy of therapy was assessed based on the reversal of symptoms and attainment of clinical normalcy. Response to therapy was graded as excellent, good, fair, and poor by assessing the clinical symptoms and lesions [8]. In all the dogs, time taken for complete recovery was also noted as per owners' statement.…”
Section: Methodsmentioning
confidence: 99%